Pengaruh Kegiatan Gerak Dasar Fisik Motorik (Lokomotor, Non Lokomotor dan Manipulatif) terhadap Kemampuan Motorik Kasar Anak Kelompok B di TK Manggarupi Kabupaten Gowa - Yahya, Wahyuni; Suardi, Suardi; Rusmayadi, Rusmayadi; Zainuddin, M. Said (Jurnal Bimbingan dan Konseling Borneo, 2024)
This research aims to 1) find out the description of basic physical motor movement activities (locomotor, non-locomotor and manipulative) before and after treatment in group B children at Manggarupi Kindergarten, Gowa Regency; 2) determine the level of achievement of gross motor skills before and after treatment in group B children at Manggarupi Kindergarten, Gowa Regency; and 3) find out whether there is an influence of basic physical motor movement activities (locomotor, non-locomotor and manipulative) on the gross motor skills of group B children in Manggarupi Kindergarten, Gowa Regency. The method in this research is an experimental method with a Quasi Experimental Design type. The sample in this study was 20 children from groups B2 and B3. The data collection technique used was checklist observation. The analysis techniques used are descriptive analysis techniques and inferential analysis. The results of the research show that there is an influence of basic physical motor movement activities (locomotor, non-locomotor and manipulative) on the gross motor skills of early childhood in Manggarupi Kindergarten, Gowa Regency by having different average data where the mean value of the experimental class is higher than the value control class mean and significance value 0.00 0.05